Synthesis and FTIR spectroscopic investigation of the UV curing kinetics of telechelic urethane methacrylate crosslinkers based on the renewable resource-cardanol - Rekha, N.; Asha, S. K. (Journal of Applied Polymer Science, 2008)
UV curable telechelic urethane-methacrylate crosslinkers based on the natural resource-cardanol was synthesized in a one pot synthetic step involving end capping of isophorone diisocyanate with one equivalent of hydroxyethyl methacrylate followed by condensation with cardanol. The structures of the resins were characterized by H-1 and C-13 NMR, fourier transform infrared (FTIR) and Matrix-assisted laser desorption/ionization time of flight (MALDI-TOF) spectroscopies and size exclusion chromatography (SEC). The curing process and double bond conversion in presence of 2,2-diethoxy acetophenone as photo-initiator upon UV irradiation was followed by Fourier transform infrared spectroscopy. These hydrogen bonded crosslinkers based on cardanol and its derivatives had higher double bond conversion when compared to a nonhydrogen bonding standard such as hexanediol diacrylate (HDDA) under identical conditions. The temperature effects on the hydrogen bonding were investigated, and a decrease in the extent of double bond conversion with increase in temperature was observed for the telechelic urethane-methacrylate crosslinkers whereas a steady increase in the curing rate was observed for HDDA. This gives direct indication of the influence of hydrogen bonding on the curing process. (C) 2008 Wiley Periodicals, Inc.
Keywords: Cardanol; hydrogen bonding; infrared spectroscopy; renewable resource; UV curing